2014
DOI: 10.7326/m13-2567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nurse-Managed Protocols in the Outpatient Management of Adults With Chronic Conditions

Abstract: U.S. Department of Veterans Affairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 50 publications
3
60
1
1
Order By: Relevance
“…More than half were females, about two thirds were married, one-third graduated from secondary school and half of them were governmental employees. This result was in the line with Shaw et al, [23] who concluded that the subject's age were ranged between thirtyseven to seventy-two with median age 58.3 years, about half of them were females.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…More than half were females, about two thirds were married, one-third graduated from secondary school and half of them were governmental employees. This result was in the line with Shaw et al, [23] who concluded that the subject's age were ranged between thirtyseven to seventy-two with median age 58.3 years, about half of them were females.…”
Section: Discussionsupporting
confidence: 81%
“…This result was also in agreement with Frisoli et al [30] who reported that lifestyle changes may postpone hypertension in non-hypertensive patients and diminish blood pressure in hypertensive patients which leads to reducing the frequency and doses of antihypertensive drugs. Also, these results were consistent with Shaw et al, [23] who reported that both systolic and DBP improved after the intervention (3.68 mmHg for SBP, 1.56 mmHg for DBP). More over, Irmak et al [24] noted a significant decrease in the mean systolic and DBP.…”
Section: 4supporting
confidence: 82%
See 1 more Smart Citation
“…The median (interquartile range) duration of hospitalization for a COPD exacerbation was less for subjects in the intervention group (5 [3][4][5][6][7][8][9][10][11] d vs 8 [4 -18.5] d, P ϭ .045). Total in-patient hospital days and ICU days due to COPD exacerbations were significantly less for the intervention group (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…5 These programs are often conducted by physician extenders and may include education about the underlying disease, optimization of evidence-based medications, support from case managers, and institution of self-management principles. 6 …”
Section: Introductionmentioning
confidence: 99%